The Legal Policy on the Prevention and Handling of Bullying in Schools - Naavi’u Emal Maaliki; Eko Soponyono (International Journal of Law Society Services, 2025)
Violence against children can cause trauma and injuries that endanger the physical and psychological condition of the victims of bullying. This paper aims to analyze the factors causing the increase in bullying behavior among students in schools and law enforcement efforts against perpetrators of bullying in educational environments. The results of the study indicate that bullying among students is generally influenced by family factors, social media, peers, and the surrounding environment. In addition, bullying acts are also triggered by ethnic differences, rejection of certain groups, physical conditions, and economic and family backgrounds. Perpetrators of child bullying can be subject to criminal sanctions or diversion according to the provisions of Law No. 35 of 2014 concerning Amendments to Law No. 23 of 2002 concerning Child Protection, as a form of deterrent effect for the perpetrators and protection for other children from bullying.